Diagnostic Delays and Treatment Implications for Patients with Isoniazid-Resistant Tuberculosis: A Case Report and Review of the Literature. (14th May 2019) - Olson, Gregory; Nathavitharana, Ruvandhi R; Lederer, Philip A
Abstract: Drug-resistant tuberculosis (DR-TB) remains a major public health threat. A 23-year-old man presented with fever, dyspnea, and a pleural effusion. After a delay, he was diagnosed with isoniazid (INH)-resistant TB. We review the literature describing the epidemiological and clinical significance of INH-resistant TB and its relevance for low-incidence countries, such as the United States.